2013
DOI: 10.1111/fwb.12112
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the crayfish plague pathogen (Aphanomyces astaci) facilitates coexistence of European and American crayfish in central Europe

Abstract: Summary 1. Most European crayfish species are strongly threatened, mainly as a result of the introduced pathogen, Aphanomyces astaci, transmitted by invasive North American crayfish. Long‐term coexistence of American and European crayfish species is therefore regarded as almost impossible, even though some coexisting populations have been observed. 2. In this study, crayfish were collected from presently coexisting populations of the introduced spiny‐cheek crayfish (Orconectes limosus) and the native noble cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…In Finland, Westman & Savolainen [56] reported a 30-year coexistence of P. leniusculus with another native species, Astacus astacus , although the latter was finally outcompeted. In these cases, it has been suggested that the invasive species was not infected by the pathogen, similarly as in some Central European sites where native crayfish coexisted with O. limosus [49]. The present situation in Lake Geneva, where we demonstrated the presence of A. astaci in five out of 16 analysed signal crayfish, seems thus different, although we cannot rule out that the pathogen has been introduced to the local population of P. leniusculus only recently.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…In Finland, Westman & Savolainen [56] reported a 30-year coexistence of P. leniusculus with another native species, Astacus astacus , although the latter was finally outcompeted. In these cases, it has been suggested that the invasive species was not infected by the pathogen, similarly as in some Central European sites where native crayfish coexisted with O. limosus [49]. The present situation in Lake Geneva, where we demonstrated the presence of A. astaci in five out of 16 analysed signal crayfish, seems thus different, although we cannot rule out that the pathogen has been introduced to the local population of P. leniusculus only recently.…”
Section: Discussioncontrasting
confidence: 48%
“…As only a small number of individuals could be tested from some sites, lack of detection of A. astaci cannot be interpreted as the absence of the pathogen from the population (see the 95% confidence intervals for the prevalence in Table 1). Providing conclusive evidence that some populations of potential A. astaci hosts (North American invasive crayfish) are likely to be uninfected requires much more intensive sampling effort [49]. Temporal fluctuations of the pathogen prevalence (or detectability) could also influence our results, as was shown for a Czech Orconectes limosus population studied over several seasons [54].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Schrimpf et al . ). However, the diagnosis of crayfish plague in susceptible species would still require tissue analysis (OIE ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the number of samples was relatively small (N = 11 to 28) and due to environmental stochasticity (Dwyer et al, 2004) or recent molting events (Oidtmann, 2012), the infection status with A. astaci may have been underestimated. The analysis of 28 individuals seems to indicate that the population from Lake Singliser is A. astaci free (Schrimpf et al, 2013b). However, a more intensive sampling could possibly still increase detection probability (95% confidence interval ranged from 0 to 12%) of A. astaci.…”
Section: Discussionmentioning
confidence: 90%